Nutrition information needs during cardiac rehabilitation: perceptions of the cardiac patient and spouse - Montgomery, D.A. (Mercy Hospital, Des Moines, IA); Amos, R.J (Journal of the American Dietetic Association, 1991)
A survey instrument, which was developed from personal interviews with participants in a cardiac rehabilitation program, was administered at two hospital-based Phase II cardiac rehabilitation programs. Thirty-five patients (28 men, 7 women) and 29 spouses (5 men, 24 women) responded to survey items designed to investigate how subjects perceived themselves dealing with the cardiac diet, what questions they were asking, and how answers to those questions would help them. Subjects in the patient group (which was 80% male) most frequently asked questions dealing with compliance and the diet's benefits. Subjects in the spouse group (which was 83% female) most frequently asked questions relating to food selection. Participants indicated that having their questions answered would help them make decisions, be motivated, feel in control, and plan. Participants' overall attitude toward the diet was positive because patients were willing to make changes in their diet; however, more than half the sample thought food labels were difficult to understand and grocery shopping was difficult. We conclude that nutrition education programs that address individual needs and uses for nutrition information could enhance the learning process in group settings such as cardiac rehabilitation programs